2011
DOI: 10.1089/scd.2010.0547
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Enhance the Engraftment and Myelinating Ability of Allogeneic Oligodendrocyte Progenitors in Dysmyelinated Mice

Abstract: Multiple sclerosis is an autoimmune disease characterized by demyelination and axonal loss throughout the central nervous system. No regenerative treatment exists for patients who fail to respond to conventional immunosuppressive and immunomodulating drugs. In this scenario, stem cell therapy poses as a rational approach for neurological regeneration. Transplantation of embryonic-derived oligodendrocyte progenitor cells (OPCs) has been shown to promote remyelination and ameliorate animal models of neurodegener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 55 publications
0
45
0
1
Order By: Relevance
“…Treated Wr mice did exhibit significant improvements in motor function, although none of these mice approached the functional capabilities of wild-type mice. The choice of SkmSCs with MSC distinctiveness as a possible cell therapy in motor neuron disorders is closely related to previous experimental evidence on MSC treatments for central nervous system (CNS) diseases (27).…”
Section: Discussionmentioning
confidence: 95%
“…Treated Wr mice did exhibit significant improvements in motor function, although none of these mice approached the functional capabilities of wild-type mice. The choice of SkmSCs with MSC distinctiveness as a possible cell therapy in motor neuron disorders is closely related to previous experimental evidence on MSC treatments for central nervous system (CNS) diseases (27).…”
Section: Discussionmentioning
confidence: 95%
“…Bai et al [22] showed that BMSCs promoted the proliferation of not only OPCs, but also neural precursor cells exiting the subventricular zone. Indeed, BMSCs or conditioned medium promoted differentiation and maturation of OPCs and influenced the differentiation fate of neural precursor cells by promoting oligodendrogenesis and inhibiting astrogliosis [1,22,51]. EGb761, a potent neuroprotective agent, can pass the BBB and protect neural cells, including oligodendrocytes and OPCs, from damage.…”
Section: Discussionmentioning
confidence: 99%
“…They can also differentiate into neurons and glial cells (6,7). The anti-inflammatory, low immunogenicity, and multipotency characteristics of BMSCs render them as a desirable cell source in regenerative medicine (6,7).…”
Section: Bone Marrow Mesenchymal Stem Cellsmentioning
confidence: 99%